ANALISIS EKUITAS BERBAGAI MEREK MINYAK GORENG - Ujang Sumarwan; Kirbrandoko Kirbrandoko; Etriya Etriya (Jurnal Manajemen & Agribisnis, 2004)
The purpose of this study was to analyzethe factors influencing brand equity of branded cooking oil. The data werecollected from 149 households living in Bogor.Cochran test, importance and performance analysis, Markov chain, anddiscriminant were used to analyze the data. The result of this study showedthat Sania position is in brand recall category. The Brand association of Saniawere yellow shine color and good packaging. Branded cooking oil users tend tobe unloyal that showed from high percentage of possibility rate of transition. Theresult suggested that Sari Agrotama Persada as Sania marketing and distributioncompany to strengthen Sania's differentiation on non preservative attribute andits brand image as healty cooking oil, and to keep its availability in alloutlets.